2022
DOI: 10.3389/fonc.2022.960720
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy assessment of the CDK4/6 inhibitor palbociclib and the PLK1 inhibitor volasertib in human chordoma xenografts

Abstract: BackgroundManagement of advanced chordomas remains delicate considering their insensitivity to chemotherapy. Homozygous deletion of the regulatory gene CDKN2A has been described as the most frequent genetic alteration in chordomas and may be considered as a potential theranostic marker. Here, we evaluated the tumor efficacy of the CDK4/6 inhibitor palbociclib, as well as the PLK1 inhibitor volasertib, in three chordoma patient-derived xenograft (PDX) models to validate and identify novel therapeutic approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…These results indicated that LRPPRC was also involved in regulating CDK4/6i sensitivity, beyond controlling CDK6 expression. The most studied functions of LRPPRC are promoting OXPHOS and cancer stem cells (CSCs) 24 , 40 , both of which have been shown to promote CDK4/6i resistance in some cancer types other than LUAD, such as glioma and bladder cancer 41 44 . Our results showed significantly increased expression of LRPPRC and OXPHOS after acquired CDK4/6i resistance in LUAD cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that LRPPRC was also involved in regulating CDK4/6i sensitivity, beyond controlling CDK6 expression. The most studied functions of LRPPRC are promoting OXPHOS and cancer stem cells (CSCs) 24 , 40 , both of which have been shown to promote CDK4/6i resistance in some cancer types other than LUAD, such as glioma and bladder cancer 41 44 . Our results showed significantly increased expression of LRPPRC and OXPHOS after acquired CDK4/6i resistance in LUAD cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, considering the limited case number and retrospective nature of this report, the evidence level of this result is relatively low. Besides, as there is a paucity of feasible biomarkers for the evaluation of CDK4/6 inhibitor sensitivity in chordoma (Passeri et al 2022 ), another limitation of this research includes that the criteria for application of Palbociclib in the current case might be controversial. Hence, the precise prediction of Palbociclib sensitivity might be undermined, and the spatial heterogeneity of the tumor cannot be completely ruled out, which possibly lead to the reduced duration of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of CDKN2A/2B, are known to play essential tumor-suppressing roles in a variety of tumors,, making this pathway an attractive therapeutic target (Helsten et al 2016 ; Kato et al 2015 ). Previous studies suggested that chordoma cells exhibiting a loss of CDKN2A (p16) may trigger universal activation of CDK4/6, implying the potential applicability of CDK4/6 inhibitor in chordoma treatment (Liu et al 2018 ) (Passeri et al 2022 ). However, no clinical evidence has ever been reported for the effectiveness of CDK inhibitors in the treatment of chordoma.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, the role of cell cycle regulation and deletion of CDKN2A in chordoma C suggests an efficiency of cell cycle targeting therapy in these patients. Inhibitor of cyclin-dependent kinases 4/6, palbociclib showed an inhibitory activity in chordoma cell lines with P16/INK4A loss [ 60 ] and more recently in 1 (out of 2) chordoma xenografts with this 9p deletion [ 61 ]. The synergistic effect of combination of rapamycin and palbociclib in chordoma cell lines with PTEN and P16/INK4A loss was also shown [ 62 ].…”
Section: Discussionmentioning
confidence: 99%